Impact of biotic interactions on biodiversity varies across a landscape. (15th June 2016) - Mod, Heidi K.; Heikkinen, Risto K.; le Roux, Peter C.; Wisz, Mary S.; Luoto, Miska
Abstract: Aim: Biotic interactions have a central role in defining species assemblages, realized both through negative and positive impacts. However, forecasts of how these interactions affect biodiversity across landscapes are challenging (and lacking) because the outcome of interactions depends not only on the identity of the interacting species but also on local environmental conditions. Thus, we study how biotic interactions manifest across a landscape. Location: High‐latitude northern Finland and Norway (69° N, 21° E). Methods: We modelled the influence of a dominant shrub, Empetrum hermaphroditum, on spatial patterns of species richness of vascular plants, bryophytes and lichens (using cover of the shrub as a proxy for the frequency and intensity of interaction with other species) across a topographically variable landscape. Results: The relationship between the cover of the dominant shrub and species richness differed between guilds, being strongest for vascular plant richness, and varied considerably along environmental gradients. The dominant shrub showed stronger negative impact on vascular plant richness under less abiotically extreme conditions. For lichens, the relationship was the opposite: under mild conditions, species richness increased with the cover of the shrub. Incorporating specific leaf area (SLA) data into analyses revealed that the dominant shrub affected species with high SLA (typically competitive species of resource‐rich environments) most negatively. Main conclusions: Our findings show how the impact of a dominant species varies across a landscape, with distinctly different effects on competitive and stress‐tolerant vascular plants, and on bryophytes and lichens. Spatial predictions of biodiversity trends under global environmental change could, therefore, critically benefit from accounting for context‐dependent impacts of biotic interactions.